2013
DOI: 10.1097/cej.0b013e328353ed81
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of soluble vascular endothelial growth factor receptor 1 (sFlt-1) in women by moderate exercise and increased plasma levels of vascular endothelial growth factor in overweight/obese women

Abstract: The incidence of breast cancer is increasing worldwide, and this seems to be related to an increase in lifestyle risk factors, including physical inactivity, and overweight/obesity. We previously reported that exercise induced a circulating angiostatic phenotype characterized by increased sFlt-1 and endostatin and decreased unbound-VEGF in men. However, there is no data on women. The present study determines the following: 1) whether moderate exercise increased sFlt-1 and endostatin and decreased unbound-VEGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
1
18
2
1
Order By: Relevance
“…While some studies have also reported effects of exercise and weight-loss on these angiogenic factors,(39,40) the studies have been small,(41,42) cross-sectional,(43) or limited to men. (44) In one study, 79 participants were randomized to a 12-week trial comparing an exercise intervention, a hypocaloric diet, and a combined arm, found that VEGF-A was non-significantly reduced by 10-22% in the weight-loss groups.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have also reported effects of exercise and weight-loss on these angiogenic factors,(39,40) the studies have been small,(41,42) cross-sectional,(43) or limited to men. (44) In one study, 79 participants were randomized to a 12-week trial comparing an exercise intervention, a hypocaloric diet, and a combined arm, found that VEGF-A was non-significantly reduced by 10-22% in the weight-loss groups.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is considered an adipokine due to its synthesis in adipose tissue and is positively correlated with increased BMI [76]. High circulating levels and increased tumoral expression of VEGF is associated with poor prognosis [77,78]. Recent studies have shown that leptin is a pro-angiogenic cytokine promoting angiogenesis, upregulating VEGF and VEGF receptors in breast cancer.…”
Section: Evidence For the Role Of Leptin In Mediating Obesity-breast mentioning
confidence: 99%
“…Brixius et al stated a decrease of endostatin plasma levels in 50–60 year old male overweight and untrained men after 6 months of moderate exercise 3 times/week [26]. However, Makey et al [27] did not find an exercise-induced increase of endostatin in overweight/obese women, but in this study the participants “only” walked on a treadmill at moderate intensity. Nevertheless, considering the results of the mentioned studies both unique and regular physical exercise seems to have an impact on endostatin levels in healthy individuals, where endostatin seems to increase during exercise and to decrease after regular sportive activity.…”
Section: Discussionmentioning
confidence: 61%